Which conditions foster high-involvement work processes? A synthesis of the literature and agenda for research. (February 2018) - Boxall, Peter; Winterton, Jonathan
High-involvement models of working are associated with high levels of worker influence over the work process, identified through worker perceptions of their jobs and working environment. This article reviews what is known about the conditions that foster the adoption of such models. Drawing on studies of worker participation in management since the 1950s, the article seeks to understand what explains the dispersion of high-involvement work processes in the private sector. In terms of understanding the potential for worker involvement in decision-making, the article argues that it is important to analyse the way in which managers develop production systems in firms. A range of conditions in manufacturing and in services are then discussed. While economic incentives are critical, the ongoing existence of societal differences, including a pronounced 'Nordic effect', suggests that economically unattractive environments do not necessarily lack opportunities to enhance worker well-being through greater involvement.